2021
DOI: 10.1155/2021/2666867
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Stimulation of the Synthesis of Preelastic Fibers in the Dermis of a Patient with Fibrosis

Abstract: Objective. The aim of the present study was to report the physiological stimulation of the synthesis of preelastic fibers in the dermis of a patient with fibrosis. Design. A clinical study was conducted involving the analysis of histological changes in preelastic fibers following treatment for stage II primary lymphedema for the clinical reversal of lymphedema and fibrosis. Setting. University Hospital of the São Jose do Rio Preto of School of Medicine in 2020. Participant was a 67-year-old male patient with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Currently evaluating the reversal of fibrosis in lower limb lymphedema and the initial results show a general change in the structure of the skin involving the entire extracellular matrix, type I and III collagen fibers, reticular fibers and epidermis as well as a novel cell type that is under analysis: telocytes. Thus, we will soon have confirmed what we have been divulging for years --that it is possible to reverse fibrosis in the treatment of lymphedema [23][24]. The limitation of the study, we believe, was that it did not include patients of the same age, the same type of surgery and post-surgery treatment (radiotherapy, chemotherapy) and similar time that lymphedema developed and to compare volume reduction with TLM (Godoy method) with other MLD techniques.…”
Section: Discussionmentioning
confidence: 85%
“…Currently evaluating the reversal of fibrosis in lower limb lymphedema and the initial results show a general change in the structure of the skin involving the entire extracellular matrix, type I and III collagen fibers, reticular fibers and epidermis as well as a novel cell type that is under analysis: telocytes. Thus, we will soon have confirmed what we have been divulging for years --that it is possible to reverse fibrosis in the treatment of lymphedema [23][24]. The limitation of the study, we believe, was that it did not include patients of the same age, the same type of surgery and post-surgery treatment (radiotherapy, chemotherapy) and similar time that lymphedema developed and to compare volume reduction with TLM (Godoy method) with other MLD techniques.…”
Section: Discussionmentioning
confidence: 85%
“…The treatment used in this study showed an important alteration in the proteins of the extracellular matrix involving type I and type III collagen and elastic fibers [ 26 , 27 ]. The development of the fibrotic process in patients with lymphedema involves the accumulation of macromolecules in the interstitial space, and this evolves with changes in extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The initial results show significant changes in type I and III collagen fibers, reticular fibers, and the epidermis, along with a novel cell type: telocytes [16,17]. Therapeutic progress depends on novel concepts and techniques with better results.…”
Section: Discussionmentioning
confidence: 99%